Antimicrobial Assessment of Curcuma longa L Against Streptococcus mutans Growth - Dohude, Gostry Aldica; Isnandar, Isnandar; Siregar, Indra Basar; Tanzia, Allisha (Dentistry Faculty, 2023)
Background. Streptococcus mutans is the most common oral endogenous microorganism found at the beginning of plaque formation until the formation of dental caries. If not handled properly, caries can lead to odontogenic infections. Increased resistance to antimicrobial drugs has made herbal ingredients an alternative treatment because they are more effective and do not cause side effects. This turmeric leaf contains active antimicrobial compounds of flavonoids, tannins, and phenolics. Objective. This study aimed to determine the effectiveness of turmeric leaf extract (Curcuma longa. L) as an antimicrobial on the growth of Streptococcus mutans bacteria. Materials and Methods. This study uses a post-test-only control condition approach in a laboratory setting. The concentration of turmeric leaf extract tested was 10%, 15%, and 20% with the positive control (Chlorhexidine 0,2% mouthwash) and negative control (DMSO) with five repetitions. Antibacterial effectiveness test using serial dilution method. Results. The data analysis using the Oneway ANOVA test showed a p-value 0.05, meaning that the number of Streptococcus mutans bacterial colonies in both the treatment and control groups had a significant difference in number. The antibacterial effect at a 10% concentration of turmeric leaf extract (Curcuma longa. L) with an average and standard deviation of 45.20 3.83, at a 15% concentration of 43.80 3.11, at a 20% concentration of 23.60 12.30. Conclusion. This study concludes that turmeric leaf extract (Curcuma longa. L) has antibacterial effectiveness against Streptococcus mutans bacteria.Keywords: Curcuma longa L, Turmeric Leaf, Streptococcus mutans, Antibacterial